Toward an Ideal Balance Of Islamic Banking Products Portfolio - Adnan, Muhammad Akhyar (Journal of Accounting and Investment, 2006)
The Islamic Banking Industry is growing rapidly in many countries, yet some important problems are yet to be faced. This includes the perception of some Muslim societies towards Islamic banking operations, accounting issues and particularly, in regard to the industries product portfolio. In the case of Indonesia – but perhaps also in the larger context – there has been concerns raised about the imbalance of product portfolio [Adnan 2003; 2005, Tohirin 2003, Muhammad 2005]. It is commonly known for example that the murabaha product has dominated product portfolio since the beginning of the industry’s operations. Although this issue is not related to fiqh concepts, many are concerned that product portfolio imbalance will cause an unevenness between the monetary or financial sector and the real sector of businesses. In other words, the situation will not reflect the notion of an Islamic economics concept, which is concerned about balance and harmony among all economic sectors. This paper offers a solution to this particular problem, with a view towards implementation of an Islamic economy.